A retrospective comparison of skin and renal direct immunofluorescence findings in patients with glomerulonephritis in adult Henoch‐Schönlein purpura. (26th February 2014) - Poterucha, Timothy J.; Wetter, David A.; Grande, Joseph P.; Gibson, Lawrence E.; Camilleri, Michael J.; Lohse, Christine M.
Abstract : Background: Henoch‐Schönlein purpura (HSP) is a vasculitis that can affect the skin and kidneys. It is characterized by immunoglobulin (Ig) A‐predominant deposition in small blood vessels. To our knowledge, there has been no comparison of direct immunofluorescence (DIF) findings in skin and kidney biopsy specimens. Methods: We retrospectively studied 21 adults with HSP who had IgA deposition in the skin and kidneys. The skin and kidney DIF findings were compared and tested for an association with the progression of renal disease. Results: Mean age of the patients was 51.4 years. Follow‐up data were available for 19 patients, of whom 5 had progression to chronic kidney disease or renal failure. Concordance between DIF findings on skin and renal biopsies was 100% for IgA, 80% for C3, 80% for IgG, 71% for IgM and 53% for fibrinogen. A worse renal outcome was associated with renal IgG deposition (p = 0.04). A trend for worse renal outcome was found with renal fibrinogen and skin IgM deposition (p = 0.10 and 0.14, respectively). Conclusions: In this retrospective study of adult HSP, the concordance between DIF findings in skin and kidney specimens was low‐moderate. Further study is required to elucidate the mechanisms responsible for these differences in Ig deposition.